Pemberdayaan Masyarakat melalui Program Penanaman Tanaman Obat Keluarga (TOGA) di Posyandu Kapodang - Timotius Agung Soripada; Haikal Misbaqun Nasir; Eka Bebasari; Dea Putri Adinda; Farhan Ardiansyah; Firza Putri Murendra; Laras Nurdianti Putri; Nashwa Khairunnisa; Nindya Auliatunnisa; Puan Nadya Khairani; Puji Satriani; Tasya Fitria; Vira Yanti (Unri Conference Series: Community Engagement, 2025)
Family Medicinal Plants (TOGA) are beneficial plants commonly cultivated in home gardens and managed directly by families as a form of easily accessible traditional medicine. In Bukit Batrem Village, limited access to health facilities and low public awareness of alternative natural remedies pose significant challenges to public health. Through the Community Service Program (KKN), our team addressed this issue by establishing a TOGA garden at the Kapodang Integrated Health Post (Posyandu), which serves as an educational tool and practical health resource. This initiative targets the Bukit Batrem community, particularly mothers and the elderly who frequently rely on Posyandu services, with the goals of: (1) increasing health independence through local medicinal plants, (2) optimizing underutilized land, and (3) reviving traditional knowledge of herbal medicine. Methods used included community outreach, direct planting (using polybags and open land), and labeling plants with scientific/local names and health benefits. Results showed an increase in community understanding of the benefits of TOGA, especially for common ailments such as hypertension (cat's whiskers), digestive problems (turmeric), and infections (galangal). The success of the program (90% target achievement) demonstrates TOGA's potential as a sustainable solution to address the health service gap in Bukit Batrem, while also encouraging environmental management.